1996
DOI: 10.1161/01.str.27.8.1399
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autoregulation in an Experimental Model of Chronic Cerebral Hypoperfusion in Rats

Abstract: It was demonstrated that (1) chronic hypoperfusion induced impairment of the upper limit of autoregulation and (2) sudden fistula closure under hypertensive conditions caused vasodilation of the arterioles. These findings suggest that rapid restoration of perfusion pressure is possibly followed by a pressure breakthrough phenomenon in a chronically hypoperfused cerebrovasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Batjer demonstrated the ability of arteries to vasodilate but an inability to vasoconstrict in response to increased pressure, a finding confirmed in a rat model [11,20,21] . We suggest that the vasoconstriction in response to SAH in our patient demonstrated that the impairment of vasoconstriction in response to elevated pressure, which has been argued to underlie NPPB syndrome, is not due to some global inability of the vasculature to constrict.…”
Section: Discussionmentioning
confidence: 76%
“…Batjer demonstrated the ability of arteries to vasodilate but an inability to vasoconstrict in response to increased pressure, a finding confirmed in a rat model [11,20,21] . We suggest that the vasoconstriction in response to SAH in our patient demonstrated that the impairment of vasoconstriction in response to elevated pressure, which has been argued to underlie NPPB syndrome, is not due to some global inability of the vasculature to constrict.…”
Section: Discussionmentioning
confidence: 76%
“…3), helping to normalize the significant disturbances in uFA and ARA-CoA concentrations evident at 6 h (Tables 1 and 2). However, autoregulation remains abnormal and the brain is more vulnerable to additional insults such as hypotension, hypoxia and further ischemia following BCCL[62]. …”
Section: Discussionmentioning
confidence: 99%
“…Brain-derived neurotrophic factor production declines with age (Sohrabji and Lewis, 2006) and is reduced by age-dependent vascular risk factors such as hypertension (Lee et al, 2006), hypoperfusion (Irikura et al, 1996), and poor glucose metabolism (Krabbe et al, 2007). Although experimental study of BDNF effects on brain aging is hampered by impossibility to manipulate human BDNF levels in vivo , natural occurring ‘mendelian randomization’ (Katan, 1986) of individuals into groups by BDNF availability presents an opportunity for an inquiry into BDNF effects.…”
Section: Introductionmentioning
confidence: 99%